Evaluation of SUV normalized by lean body mass (SUL) in 68Ga-PSMA11 PET/CT: a bi-centric analysis - Andrei Gafita; Jeremie Calais; Charlott Franz; Isabel Rauscher; Hui Wang; Andrew Roberstson; Johannes Czernin; Wolfgang A. Weber; Matthias Eiber (EJNMMI Research, 2019)
Abstract Introduction The aim of this analysis was to investigate whether the standardized uptake value (SUV) normalized by lean body mass (SUL) is a more appropriate quantitative parameter compared to the commonly used SUV normalized by patient’s weight in 68Ga-PSMA11 PET/CT. Material and methods 68Ga-PSMA11 PET/CT scans of 121 patients with prostate cancer from two institutions were evaluated. Liver SUV was measured within a 3-cm volume-of-interest (VOI) in the right hepatic lobe and corrected for lean body mass using the Janmahasatian formula. SUV and SUL repeatability between baseline and follow-up scans of the same patients were assessed. Results SUV was significantly positively correlated with body weight (r = 0.35, p = 0.02). In contrast, SUL was not correlated with body weight (r = 0.23, p = 0.07). No significant differences were found between baseline and follow-up scan (p = 0.52). Conclusion The Janmahasatian formula annuls the positive correlations between SUV and body weight, suggesting that SUL is preferable to SUV for quantitative analyses of 68Ga-PSMA11 PET/CT scans.